2022
DOI: 10.1172/jci.insight.161698
|View full text |Cite
|
Sign up to set email alerts
|

In vivo killing of primary HIV-infected cells by peripheral-injected early memory–enriched anti-HIV duoCAR T cells

Abstract: HIV-specific chimeric antigen receptor–T cell (CAR T cell) therapies are candidates to functionally cure HIV infection in people with HIV (PWH) by eliminating reactivated HIV-infected cells derived from latently infected cells within the HIV reservoir. Paramount to translating such therapeutic candidates successfully into the clinic will require anti-HIV CAR T cells to localize to lymphoid tissues in the body and eliminate reactivated HIV-infected cells such as CD4 + T cells and monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…This supports an earlier report that HIV-infected macrophages are susceptible to HIV-specific CAR T cells [65]. Recently, duo CAR T cells, which are created using autologous T cells transduced with two CAR constructs (mD1.22-CAR and m36.4-CAR), eliminated HIV-infected splenic PBMCs of humanized mice, along with infected CD4 + T cells and monocytes in vitro [82 ▪▪ ]. These are currently being tested in a Phase I/IIa clinical trial in PLWH (NCT04648046).…”
Section: Harnessing Immune Cells For Viral Controlsupporting
confidence: 87%
“…This supports an earlier report that HIV-infected macrophages are susceptible to HIV-specific CAR T cells [65]. Recently, duo CAR T cells, which are created using autologous T cells transduced with two CAR constructs (mD1.22-CAR and m36.4-CAR), eliminated HIV-infected splenic PBMCs of humanized mice, along with infected CD4 + T cells and monocytes in vitro [82 ▪▪ ]. These are currently being tested in a Phase I/IIa clinical trial in PLWH (NCT04648046).…”
Section: Harnessing Immune Cells For Viral Controlsupporting
confidence: 87%
“…In addition, these variable domains fall victim to the same shortcomings that their parent monoclonal and bNAbs faced, an inability to accurately target the gp120 protein. A current study is using lentiviral vectors to mediate CAR-modification of T cells to present these anti-HIV CARs (i.e., duoCARs) and make cells resistant to HIV-1 [ 41 , 67 ]. Other novel CAR-T-cell technologies are being developed to recognize, bind, and kill MHC–antigen complexes, but these methods are predominantly in the pre-clinical development stage for various malignancies [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lentiviral-based gene modification is used to generate CAR-T cells for HIV-1 cure in patients who are otherwise healthy and stably suppressed on ART (ClinicalTrials.gov #NCT04648046) [ 41 , 67 ]. While the cells transduced with lentiviral vectors make RNA transcripts that code for CARs or other products of interest in gene therapy studies, they are engineered to avoid lentiviral replication [ 79 , 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, macrophages are particularly hard to be targeted by the host CD8 + T-cells [74], and may resist killing while maintaining inflammatory functions [75]. Interestingly, recent data in vitro showed that this resistance to cell death in macrophages may not be maintained against CAR-T cells [75,76 ▪▪ ], despite the low env antigen density on the surface of those cells [77]. Nonetheless, in vivo data are still lacking, and whether these findings also apply to brain-resident microglia is still unknown.…”
Section: Therapeutic Vaccination and Cell-based Therapiesmentioning
confidence: 99%